Crosslinked Protein Delivery Strategy with Precise Activity Regulation Properties for Cancer Therapy and Gene Editing. Issue 8 (27th January 2022) - Liu, Ning; Zhu, Lianghan; Sun, Honghao; Zhou, Zhanwei; Dong, Jingwen; Sun, Minjie
Abstract: Protein drugs hold tremendous promise for therapeutic applications due to their direct and superior pharmacological effects. However, protein drugs can be degraded in blood stream and unable to cross many physical barriers to exert therapeutic effect. Degradable synthetic crosslinking is a versatile strategy to enhance the stability of the nanoparticle in a complex physiological medium and is helpful to get through physical barriers. Herein, crosslinked polypeptide (PABP) composed of poly‐amino acids including cystine, tyrosine, lysine, ketal bridge, and polyethylene glycol (PEG) is modularly explored and synthesized for protein delivery. Notably, plasma membrane V‐ATPase is the particular pathway which induces the macropinocytosis of the inner peptide analogous core (PAB/protein) after the outer PEG shell disassociation at tumor intercellular sites. In addition, PABP/protein achieves proteins' activity shielding in systemic circulation and recovery in tumor cytoplasm precisely. In application, PABP/RNase‐A shows satisfying tumor accumulation and antineoplastic efficacy. More importantly, PABP/Cas9 + small guide RNA displays obvious gene editing efficiency. The crosslinked protein delivery strategy not only makes the accurate protein transport and activity regulation possible but also is promising in paving the way for clinical translation of protein drugs. Abstract : Degradable synthetic crosslinking is a versatile strategy to enhance the stability of nanomaterials in a complex physiological medium while controlling their disassembly in specific conditions. Accordingly, a kind of crosslinked poly‐amino acid delivering various protein drugs to achieve accurate protein activity regulation and application in cancer therapy and gene editing is constructed.